2020
DOI: 10.1371/journal.pone.0239746
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of fusion based planet-scope and Sentinel-2 data for crop classification using inception inspired deep convolutional neural network

Abstract: This research work aims to develop a deep learning-based crop classification framework for remotely sensed time series data. Tobacco is a major revenue generating crop of Khyber Pakhtunkhwa (KP) province of Pakistan, with over 90% of the country's Tobacco production. In order to analyze the performance of the developed classification framework, a pilot sub-region named Yar Hussain is selected for experimentation work. Yar Hussain is a tehsil of district Swabi, within KP province of Pakistan, having highest con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Bilinear interpolation is a technique used to shift digital images to various sampling rasters. After that, the normalized difference vegetation index (NDVI) was calculated (Equation ) (Minallah et al., 2020). NDVIbadbreak=NIRRLNIR+RL,$$\begin{equation} NDVI = \frac{NIR - RL}{NIR + RL} ,\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…Bilinear interpolation is a technique used to shift digital images to various sampling rasters. After that, the normalized difference vegetation index (NDVI) was calculated (Equation ) (Minallah et al., 2020). NDVIbadbreak=NIRRLNIR+RL,$$\begin{equation} NDVI = \frac{NIR - RL}{NIR + RL} ,\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…Convolutional neural networks are a class of ANNs that has proven their effectiveness in the area of image recognition and classification. Recently, deep CNNs [18] are making inroads in other areas and are performing well. Vrskova et al, [19] performed a hyper-parameter case study on in buildings vegetation detection using CNN.…”
Section: Related Workmentioning
confidence: 99%
“…Ground truth data from the study area was collected at the end of September 2020 using an locally designed geo-survey mobile application [12]. The amount of data collected during the ground survey of all the classes considered for this study is shown in Table 1.…”
Section: Data Preparationmentioning
confidence: 99%